2011
DOI: 10.1093/ecam/nen079
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine: Comparison of Current Knowledge, Attitudes and Interest among German Medical Students and Doctors

Abstract: Although it has been agreed that complementary and alternative medicine (CAM) should be included in the German medical curriculum, there is no consensus on which methods and how it should be taught. This study aimed to assess needs for CAM education by evaluating current knowledge, attitudes and interests of medical students, general physicians and gynecologists. Two instruments based on established and validated questionnaires were developed. One was given to seventh semester medical students and the other to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 43 publications
4
44
0
8
Order By: Relevance
“…Similarly, results obtained in other surveys (5)(6)(7)(8)(9)(10)(11) indicated that the majority of medical students is interested in learning the fundamentals of homeopathy and acupuncture and are favorable to include ting these disciplines in the undergraduate curriculum. Although a significant number of interviewees ignored the main reasons for use of these unconventional therapies, as well as their effectiveness, most of them defended the use of these medical specializations in public health care, for integration with conventional medicine, seeking to increase the physicianpatient relationship and to enlarge the spectrum of action of the medical art.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, results obtained in other surveys (5)(6)(7)(8)(9)(10)(11) indicated that the majority of medical students is interested in learning the fundamentals of homeopathy and acupuncture and are favorable to include ting these disciplines in the undergraduate curriculum. Although a significant number of interviewees ignored the main reasons for use of these unconventional therapies, as well as their effectiveness, most of them defended the use of these medical specializations in public health care, for integration with conventional medicine, seeking to increase the physicianpatient relationship and to enlarge the spectrum of action of the medical art.…”
Section: Discussionmentioning
confidence: 59%
“…In Oman, herbal remedies are considered as over the counter (OTC) drugs and thus are easily available through pharmacies. This is reported in literature that medical students and general practitioner both have an opinion that CAM should be included in the curriculum [11].…”
Section: Discussionmentioning
confidence: 97%
“…Em revisão sistemática da literatura sobre as PIC no ensino médico, Christensen 15 Resultados similares obtidos em outras pesquisa [15][16][17][18][19][20][21] indicaram que a maioria dos estudantes de medicina está interessada em estudar os fundamentos da homeopatia e acupuntura, e é favorável à inclusão destas disciplinas no currículo de graduação. Assim, embora um número significante de participantes ignore as principais razões para usar as terapias não convencionais, assim como sua efetividade, eles defendem seu uso no sistema público de saúde, para integrar a medicina convencional, procurando melhorar a relação médico-paciente e aumentar o espectro de ação da arte médica.…”
Section: Discussãounclassified